Therapeutic effects of standardized fenugreek seed extract on experimental urolithiasis in rats - Chinmay U. Kapase, Subhash L. Bodhankar, Vishwaraman Mohan, Prasad A. Thakurdesai (Journal of Applied Pharmaceutical Science, 2013)
The objective of the present study was to investigate therapeutic efficacy of standardized fenugreek seed extract with trigonelline as marker (SFSE-T) in experimental urolithiasis in rats. Effects of subacute oral treatments of SFSE-T (30 and 60 mg/kg) and reference anti-urolithiasis drug, Cystone (750 mg/kg) were evaluated against 0.75% ethylene glycol (EG) and 1 % w/v ammonium chloride (AC) induced urolithiasis in rats. The biochemical (urinary and serum) and histopathological parameters were investigated. Subacute oral treatment of SFSE-T (60 mg/kg) showed reversal of EG+AC induced changes in urine (decreased 24-h urine output, pH, excretion of creatinine, citrate, and chloride and increased uric acid and oxalate excretion) and serum (increased creatine, uric acid and blood urea nitrogen) parameters and decreased creatine clearance. Histopathology examination of the kidneys sections from SFSE-T (60 mg/kg) treated rats showed lowered number of crystals, cell damage and tubulointerstitial damage index as compared with EG+AC control rats. Standardized fenugreek seed extracts showed promising therapeutic effect against experimental urolithiasis in rats.
Keywords: Fenugreek, trigonelline, therapeutic, urolithiasis